2011
DOI: 10.3109/09513590.2010.487584
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GPR30, ERα and ERβ in endometrium during window of implantation in patients with polycystic ovary syndrome: a pilot study

Abstract: Women with polycystic ovary syndrome (PCOS) exhibit a lower pregnancy rate, which may be related to decreased estrogen receptor (ER) expression or endometrial receptivity. We measured expression of ERα, ERβ and the novel G protein-coupled ER (GPR30) in endometrium during window of implantation (WOI) in PCOS patients. Fifteen Chinese women with PCOS were compared to 15 normal subjects. Serial trans-vaginal ultrasonic scanner (TVUS) examinations detected follicular development, and endometrial thickness and patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 9 publications
0
14
2
1
Order By: Relevance
“…Additionally, in a recent study, the nuclear localization of GPER was demonstrated in fibroblasts, indicating that GPER also mediates a nuclear signaling pathway [23]. Moreover, two recent studies demonstrated nuclear GPER expression in eutopic endometrial cells [24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in a recent study, the nuclear localization of GPER was demonstrated in fibroblasts, indicating that GPER also mediates a nuclear signaling pathway [23]. Moreover, two recent studies demonstrated nuclear GPER expression in eutopic endometrial cells [24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…PRB has been shown to physically associate with ERβ in rat uterine stromal cells [38], and it has been shown that treatment with E2 induces PRB expression more than PRA expression in human endometrium [39]. Although increased PR expression [34] and decreased ERβ expression are seen in women with PCOS compared to controls [40], how epithelial cell proliferation is regulated in vivo by the coordinated interaction of stromal PR and ERβ in women with PCOS has yet to be determined.…”
Section: Reviewmentioning
confidence: 99%
“…Early abortion accounts for most of the pregnancy failures (Jakubowicz et al, 2002). Abnormal hormonal environments and inflammatory factor expression in vivo can lead to endometrial maldevelopment (Quezada et al, 2006;Villavicencio et al, 2006), which affects embryo implantation (i.e., endometrial receptivity) (Wang, et al, 2011). Even if spontaneous ovulation occurs, the pregnancy rate is low and the early abortion rate is high.…”
Section: Introductionmentioning
confidence: 98%